MODELLING AND CONTROL SYSTEM DESIGN TANJUNG PRIOK COMBINED CYCLE POWER PLANT - CAHYONO (NIM:23108315); Pembimbing : DR. Ir. Indrawanto, HARI
Priok Combined Cycle Power Plant Systems has a lot of variables that include the system of Gas Turbine Generator (GTG), Heat Recovery Steam Generator (HRSG), and Steam Turbine Generator (STG) complete with excitation system and Automatic Voltage Regulator (AVR) with varying load characteristics. Priok Combined Cycle Power Plant is an important provider of electrical power so that it needs a modeling and dynamical control system studies to evaluate the performance of control system. Model system that created consist of gas turbine generator (GTG) is isolated without connecting to the electricity network, GTG Single Machine Infinite Bus, STG Single Machine Infinite Bus, load frequency control model with two GTG and one block combined cycle power plant, and one block combined cycle power plant with excitation & AVR systems connected in an electrical network. Control design stage begins with the formation of matrix state space from the model that has been created and used as an Optimal Linear Quadratic Regulator (LQR) control system. LQR Optimal control of the application on several variations of the model which made the result is a control system designed its proven able to control frequency, load and voltage. In controlling the frequency and the load is carried by several power plant of power sharing interaction that compensate for each loads, so that changes in frequency will reduced toward the nominal frequency. The simulation result prove that more power plants that participate in load frequency control, the smaller the change in frequency and the load on each plant. The simulation result also show that the model of control system for Combined Cycle Power Plant multi-machine complete with & AVR excitation system can minimize the change in frequency, load and voltage to steady within 1.5-2 seconds, so this system better than the load frequency control.